MERMUMUSKAN IDE SOLUSI DIGITAL MELALUI METODE DESAIN THINKING - Afrizal, Yogi Hady; Salam, Muhammad Fachrul; Hilalulya, Hilalulya (Al-Mulk: Jurnal Pengabdian Masyarakat, 2024)
This activity is a form of Indonesia's attention to bringing out new seeds of young innovators in digital business. with the Hack4ID activity which was organized by the National 1000 startup movement in Makassar City for 2 days with the participation of as many teams as the topic of logistics in MSMEs which produced brilliant ideas that were ready to be tested. This activity was carried out using the design thinking method where participants were faced with initial user problems to create ideas as solutions to the initial problems they encountered from their users.Keywords: Startup; Desain Thinking; Inovasi; Digital.